Thermosensitive discoloration-reflective insulation difunctional water-based paint and preparation method thereof
By preparing temperature-sensitive discoloration-infrared reflective hybrid nanoparticles and zwitterionic temperature-sensitive grafted polymer microspheres, the functional fragmentation problem of temperature-sensitive discoloration coatings and reflective thermal insulation coatings is solved, the efficient fusion of the coating is achieved, the color discoloration uniformity and thermal insulation efficiency are improved, and it is suitable for the coating needs of various scenarios.
Patent Information
- Application Number
- CN202511041108.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-28
- Publication Date
- 2025-08-29
AI Technical Summary
The existing temperature-sensitive color-changing coatings and reflective heat-insulating coatings have functional cleavage, poor compatibility and insufficient weather resistance, which cannot achieve efficient fusion of temperature-sensitive color-changing and reflective heat-insulation, resulting in uneven color discoloration, low thermal insulation efficiency and long-term use performance attenuation.
By preparing temperature-sensitive discoloration-infrared reflection hybrid nanoparticles and zwitterionic thermosensitive grafted polymer microspheres, combining components such as aqueous polyurethane, and synergistic methods of physical dispersion and chemical action are adopted to achieve uniform dispersion and stable bonding of functional particles, forming nanoparticles with core-shell structures, enhancing interface binding force and weather resistance.
It significantly improves the comprehensive performance of the paint, achieves efficient integration of temperature-sensitive discoloration and reflective thermal insulation functions, significantly improves the uniformity of the coating color discoloration and thermal insulation efficiency, and enhances weather resistance. It is suitable for scenes such as building exterior walls, industrial equipment and transportation tools.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional coatings, and in particular to a temperature-sensitive color-changing and reflective heat-insulating dual-functional water-based coating and a preparation method thereof. Background Art
[0002] With the continued growth of global energy demand and the rapid development of building energy-saving technologies, functional coatings, as a key vehicle for achieving environmental responsiveness and energy-saving regulation, have become a research and development hotspot in the materials field. Traditional coatings are mostly single-function, such as decorative coatings that focus solely on color and weather resistance, and protective coatings that emphasize corrosion protection and wear resistance. These coatings struggle to meet the dual demands of "intelligent responsiveness + energy-saving regulation" in complex scenarios. Against this backdrop, dual-functional coatings that combine environmental sensing and functional regulation are gradually becoming a research focus. The combination of temperature-sensitive color change and reflective thermal insulation has attracted significant industry attention due to its ability to simultaneously achieve "visual temperature monitoring" and "active heat energy blocking."
[0003] However, existing thermochromic coatings have significant performance bottlenecks. Their core functional groups are mostly organic dyes or inorganic phase change materials. The former (such as spiropyrans) have high color change sensitivity, but their polarity differs greatly from that of water-based resins. They easily aggregate to form agglomerates during dispersion, resulting in spots or color differences on the coating surface. The latter (such as semiconductor particles) have better stability, but their surface energy is high, resulting in weak interfacial bonding with the water-based system. They are prone to phase separation after long-term use, affecting film-forming properties and mechanical properties. In addition, the thermosensitive groups lack weather resistance and are easily degraded by environmental factors such as ultraviolet rays and humidity, causing the color change effect to decay over time, limiting their application in outdoor buildings, transportation facilities, and other scenarios.
[0004] Reflective thermal insulation coatings also face the problems of single functionality and insufficient stability. Their core relies on the reflection of near-infrared light by highly reflective fillers (such as hollow glass microspheres). However, the filler surface is highly inert and has poor compatibility with resins, requiring the addition of dispersants or coupling agents. This not only increases cost but also may introduce impurities that affect coating performance. A single filler has limited reflective efficiency for near-infrared light, making it difficult to meet the demand for efficient thermal insulation. More critically, the surface properties of the filler (such as polarity and roughness) required for both thermochromic and reflective insulation functions conflict with each other. The thermosensitive group requires specific polarity to achieve reversible color change, while the reflective filler requires low surface energy to reduce energy absorption. This makes it difficult to achieve functional synergy in the development of dual-functional coatings. Existing products often suffer from problems such as uneven color change, low thermal insulation efficiency, and long-term performance degradation, making it impossible to achieve the integrated application of "temperature-responsive color development + intelligent temperature control and thermal insulation." Summary of the Invention
[0005] The purpose of the present invention is to provide a temperature-sensitive color-changing and reflective heat-insulating dual-functional water-based coating and a preparation method thereof, which solves the technical problems of functional separation, poor compatibility and insufficient weather resistance of existing temperature-sensitive color-changing coatings and reflective heat-insulating coatings.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A temperature-sensitive color-changing and reflective heat-insulating dual-functional water-based coating, comprising the following raw materials in parts by weight:
[0008] Waterborne polyurethane: 250-450 parts by weight;
[0009] Thermochromic-infrared reflective hybrid nanoparticles: 50-100 parts by weight;
[0010] Zwitterionic thermosensitive grafted polymer microspheres: 200-350 parts by weight;
[0011] Dipropylene glycol butyl ether: 20-50 parts by weight;
[0012] Silicone defoamer: 1-3 parts by weight;
[0013] Acrylate leveling agent: 2-5 parts by weight;
[0014] Biassociative polyurethane thickener: 3-8 parts by weight;
[0015] Deionized water: 250-400 parts by weight;
[0016] Among them, the preparation method of the thermosensitive color-changing-infrared reflective hybrid nanoparticles includes: A1, mixing indium chloride and tin chloride in ethylene glycol solvent, adding concentrated hydrochloric acid, reflux reaction at 180-182°C, and centrifugation and washing to obtain ITO nanoparticles; dispersing the ITO nanoparticles in anhydrous ethanol, adding ammonia water to adjust the pH to 8.9-9.1, slowly adding tetraethyl orthosilicate, and stirring at 40-42°C to obtain SiO2@ITO; A2, dispersing SiO2@ITO in toluene, adding aminopropyltriethoxysilane, reflux reaction at 80-82°C, and centrifugation and washing to obtain amino-modified SiO2@ITO; dispersing the amino-modified SiO2@ITO in anhydrous ethanol, adding spiropyran, reacting at 60-62°C, centrifugation and washing until neutral, vacuum drying at 40-42°C, and grinding and sieving.
[0017] According to a preferred embodiment of the present invention, the waterborne polyurethane is purchased from Wanhua Chemical Group Co., Ltd., and the model is WANOL® PU-2000.
[0018] According to a preferred embodiment of the present invention, the indium chloride is purchased from Zhuzhou Torch Industrial Furnace Co., Ltd., and the model is InCl3·4H2O (analytical grade).
[0019] According to a preferred embodiment of the present invention, the tin chloride is purchased from Yunnan Tin Industry Co., Ltd., and the model is SnCl4·5H2O (industrial grade).
[0020] According to a preferred embodiment of the present invention, the ethylene glycol is purchased from Sinopec Shanghai Petrochemical Co., Ltd., and the model is EG-200 (industrial grade).
[0021] According to a preferred embodiment of the present invention, the concentrated hydrochloric acid is purchased from Xinjiang Tianye (Group) Co., Ltd., and the model is 36% industrial grade concentrated hydrochloric acid.
[0022] According to a preferred embodiment of the present invention, the anhydrous ethanol is purchased from COFCO Biotechnology Co., Ltd. and the type is anhydrous ethanol (analytical grade, ≥99.7%).
[0023] According to a preferred embodiment of the present invention, the ammonia water is purchased from Luxi Chemical Group Co., Ltd. and the type is 25%-28% industrial ammonia water.
[0024] According to a preferred embodiment of the present invention, the tetraethyl orthosilicate was purchased from Hubei Xingfa Chemical Group Co., Ltd., and the model number was TEOS-98% (industrial grade).
[0025] According to a preferred embodiment of the present invention, the toluene is purchased from Sinopec Corporation and is of the type of toluene (industrial grade, ≥99.5%).
[0026] According to a preferred embodiment of the present invention, the aminopropyltriethoxysilane is purchased from Nanjing Shuguang Silane Chemical Co., Ltd., and the model number is KH-550 (industrial grade).
[0027] According to a preferred embodiment of the present invention, the spiropyran was purchased from Beijing Coupling Technology Co., Ltd., and the model number was SP-1 (pure photochromic product).
[0028] According to a preferred embodiment of the present invention, the dipropylene glycol butyl ether is purchased from Jiangsu Yida Chemical Co., Ltd., and the model is DPNB-industrial grade (≥99%).
[0029] According to a preferred embodiment of the present invention, the organosilicon defoamer is purchased from Jiangsu Sixin Technology Applied Chemical Co., Ltd., and the model number is XH-200 (water-based organosilicon defoamer).
[0030] According to a preferred embodiment of the present invention, the acrylic ester leveling agent is purchased from Wanhua Chemical Group Co., Ltd., and the model number is ACRYLATIC® 3100 (water-based acrylic ester leveling agent).
[0031] According to a preferred embodiment of the present invention, the di-associative polyurethane thickener is purchased from Hengyu Chemical Co., Ltd., and the model number is RM-8W (water-based associative polyurethane thickener).
[0032] In this invention, the preparation of thermochromic-infrared-reflecting hybrid nanoparticles is divided into three core stages, each of which achieves functional coupling through specific interfacial reactions and material transformations. The first stage involves the formation of the inorganic core: a metal salt compound is mixed with an acidic solvent and then subjected to a high-temperature reflux reaction. The metal cations are reduced or hydrolyzed in the acidic environment, gradually aggregating to form an inorganic nanocore structure with a specific crystal form. During this process, the acidic conditions not only promote the dissolution and dissociation of the metal salt but also provide a suitable reaction environment for the growth of the nanocore. By controlling the reaction temperature and time, the size and morphology of the nanocore can be adjusted. The second stage involves the surface coating of the inorganic core: the inorganic nanocore is dispersed in a polar aprotic solvent, a silicon-containing precursor and an alkaline modifier are added, and a continuous inorganic shell is constructed on the core surface through a sol-gel reaction. The silicon-containing precursor undergoes hydrolysis under alkaline conditions to generate hydroxyl-containing intermediates. These hydroxyl groups form covalent bonds with active sites (such as hydroxyl groups or oxygen anions) on the nanocore surface through condensation reactions, gradually accumulating to form the shell structure. The thickness and density of the shell can be precisely controlled by adjusting the precursor concentration, reaction temperature, and reaction time, ultimately forming composite particles with a stable core-shell structure. The third stage involves the grafting of functional groups: core-shell particles with surface active sites are dispersed in a nonpolar solvent. An organosilicon compound containing reactive functional groups is added, and thermosensitive functional groups are introduced onto the shell surface via a hydrolysis-condensation reaction. The active groups (such as epoxy) of the organosilicon compound undergo condensation with the hydroxyl groups on the shell surface, forming stable chemical bonds, thereby anchoring the thermosensitive groups to the particle surface. During this process, the polarity of the solvent and the reaction temperature directly influence the reactivity of the functional groups. Controlling the reaction conditions ensures that the functional groups are evenly and stably anchored to the particle surface, preventing aggregation or detachment.
[0033] According to a preferred embodiment of the present invention, in step A1, the reflux reaction time at 180-182° C. is 2-4 h; the centrifugation speed is 10,000-11,000 rpm for 10-20 min; and the stirring time at 40-42° C. is 3-4 h.
[0034] According to a preferred embodiment of the present invention, in step A2, the reflux reaction time at 80-82°C is 6-8 hours; the reaction time at 60-62°C is 4-6 hours; the vacuum drying time at 40-42°C is 12-14 hours; and the product is ground through a 300-320 mesh sieve.
[0035] According to a preferred embodiment of the present invention, the preparation method of the zwitterionic thermosensitive grafted polymer microspheres includes: B1, adding deionized water, styrene, and sulfonated betaine to a reactor, adding potassium persulfate after nitrogen deoxygenation, and reacting at 70-72°C to obtain polystyrene-sulfonated betaine microspheres; B2, dispersing the polystyrene-sulfonated betaine microspheres in N,N-dimethylformamide, adding a thermosensitive monomer, ethyl 2-bromoisobutyrate, CuBr, and pentamethyldiethylenetriamine, and reacting at 60-62°C; after the reaction is completed, precipitating with methanol and centrifuging and washing.
[0036] According to a preferred embodiment of the present invention, the deionized water is purchased from Shanghai Precision Scientific Instrument Co., Ltd. and is industrial-grade deionized water (conductivity ≤ 10 μS / cm) prepared by a UPW-1000 ultrapure water machine.
[0037] According to a preferred embodiment of the present invention, the styrene is purchased from the Zhenhai Refining and Chemical Company of Sinopec, and the type is industrial-grade styrene (purity ≥99.5%).
[0038] According to a preferred embodiment of the present invention, the sulfobetaine is purchased from Jiangsu Feixiang Chemical Co., Ltd., and the model is BS-12 (dodecyldimethylsulfobetaine, industrial grade).
[0039] According to a preferred embodiment of the present invention, the reactor was purchased from Weihai Chemical Machinery Co., Ltd., and its model is RJ-500L stainless steel reactor (volume 500L, jacket heating).
[0040] According to a preferred embodiment of the present invention, the nitrogen is purchased from Hangzhou Oxygen Generator Group Co., Ltd., and the model is GZ-50 industrial nitrogen cylinder (purity ≥99.99%).
[0041] According to a preferred embodiment of the present invention, the potassium persulfate is purchased from Tianjin Kemeiou Chemical Reagent Co., Ltd., and the type is analytically pure potassium persulfate (K2S2O8, purity ≥99.0%).
[0042] According to a preferred embodiment of the present invention, the N,N-dimethylformamide is purchased from Jiangsu Feixiang Chemical Co., Ltd. and is industrial-grade N,N-dimethylformamide (DMF, purity ≥99.5%).
[0043] According to a preferred embodiment of the present invention, the temperature-sensitive monomer is purchased from Aladdin Reagent (Shanghai) Co., Ltd., and the model is N-isopropylacrylamide (NIPAM, polymerization grade, purity ≥99%).
[0044] According to a preferred embodiment of the present invention, the ethyl 2-bromoisobutyrate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and the model was 2-Bromo-2-methylpropionic acid ethyl ester (CAS No. 600-00-0, purity ≥98%).
[0045] According to a preferred embodiment of the present invention, the CuBr is purchased from Shanghai MacLean Biochemical Technology Co., Ltd., and the type is anhydrous cuprous bromide (CuBr, purity ≥99%).
[0046] According to a preferred embodiment of the present invention, the pentamethyldiethylenetriamine is purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd., and the model is PMDETA (pentamethyldiethylenetriamine, purity ≥98%).
[0047] According to a preferred embodiment of the present invention, the high-speed disperser is purchased from Shanghai Modern Environmental Engineering Technology Co., Ltd., and the model is SFJ-400 high-speed disperser (motor power 7.5kW, speed range 0-2800rpm).
[0048] In the present invention, the preparation of zwitterionic thermosensitive grafted polymer microspheres is centered around free radical polymerization and atom transfer radical polymerization, with functional integration achieved through monomer polymerization and chain segment grafting. The first stage is the initial formation of the polymer microspheres: a water-soluble monomer, a zwitterionic monomer, and an initiator are mixed under an inert atmosphere and heated to the reaction temperature to initiate the polymerization reaction. The initiator decomposes to produce free radicals, which attack the double bonds of the monomers, activating them. The activated monomer molecules are then gradually linked into chains through addition reactions, ultimately forming a microsphere structure with a water-soluble polymer as the backbone. The introduction of the zwitterionic monomer imparts amphiphilic groups (e.g., positively and negatively charged groups) to the microsphere surface, imparting excellent dispersion stability and preventing particle aggregation in the medium. The second stage involves the grafting modification of the thermosensitive chain segments: the initially formed polymer microspheres are dispersed in a polar aprotic solvent, followed by the addition of the thermosensitive monomer, a transition metal catalyst, and a ligand. The thermosensitive chain segments are then grafted onto the microsphere surface via atom transfer radical polymerization. A transition metal catalyst (such as cuprous bromide) and a ligand (such as pentamethyldiethylenetriamine) form a catalytic system, initiating the polymerization of the thermosensitive monomer. The double bonds of the thermosensitive monomer are activated by the catalyst, undergoing chain transfer reactions with active sites on the microsphere surface (such as halogen end groups), gradually grafting the thermosensitive chain segments onto the microsphere surface. During this process, the cyclic regeneration of the catalyst and the gradual consumption of the monomers enable controlled growth of the chain segments, ultimately forming a functional layer with uniform thickness and thermosensitive properties on the microsphere surface. The third stage is stabilization of the functional layer: After the reaction, unreacted monomer and catalyst are removed through physical methods such as precipitation and centrifugation, resulting in polymer microspheres with surface-grafted thermosensitive chain segments. The thermosensitive chain segments undergo conformational changes (such as curling or uncurling) at specific temperatures. This chain movement alters the surface roughness and refractive index of the microspheres, thereby enabling dynamic control of near-infrared light reflection. The presence of zwitterionic groups strengthens the interfacial adhesion between the microspheres and the waterborne resin through hydrogen bonding with water molecules, preventing phase separation of the coating during use.
[0049] According to a preferred embodiment of the present invention, in step B1, the reaction time at 70-72° C. is 12-14 h.
[0050] According to a preferred embodiment of the present invention, in step B2, the reaction time at 60-62° C. is 24-26 h.
[0051] The present invention also provides a method for preparing the temperature-sensitive color-changing and reflective heat-insulating dual-function water-based coating, comprising the following steps:
[0052] S1. Add waterborne polyurethane to a high-speed disperser, followed by deionized water, thermochromic-infrared reflective hybrid nanoparticles, and zwitterionic thermosensitive grafted polymer microspheres, and pre-disperse until no obvious agglomeration occurs.
[0053] S2. Add dipropylene glycol butyl ether, silicone defoamer, and acrylic leveling agent and stir at low speed;
[0054] S3. Slowly add associative polyurethane thickener to adjust the viscosity to 50-80 mPa·s, filter and package.
[0055] In this invention, the coating preparation process achieves functional integration and performance optimization of each component through the synergistic combination of physical dispersion and chemical reactions. The first stage involves pre-dispersion of the binder and functional particles. A water-based polyurethane is used as the film-forming binder. The polar groups (such as hydroxyl and carboxyl groups) on its molecular chains form hydrogen bonds with water, imparting excellent fluidity to the system. Thermochromic-infrared-reflective hybrid nanoparticles and zwitterionic thermosensitive grafted polymer microspheres are then added to the binder. High-speed mechanical shear (such as the rotation and shear force of a disperser) overcomes the van der Waals forces and electrostatic repulsion between the particles, resulting in uniform dispersion of the particles in the aqueous medium. During this process, the entanglement of the binder's molecular chains and the hydrogen bonding between active sites (such as hydroxyl and amino groups) on the particle surfaces and water contribute to maintaining the stability of the dispersion and preventing coating defects caused by particle agglomeration. The second stage involves the addition and functional adjustment of additives. Coating agents, defoamers, and leveling agents are added to the dispersion to optimize the coating's film-forming properties by reducing surface tension, eliminating bubbles, and improving flow. Coalescents form hydrogen bonds with polar groups (such as hydroxyl groups) in the binder's molecular chains, lowering the binder's glass transition temperature and promoting uniform film formation at low temperatures. Defoamers reduce the liquid's surface tension, forming an unstable liquid film on the surface of bubbles, causing them to burst and escape. Leveling agents form an extremely thin adsorption layer on the coating surface, reducing the surface tension difference between the liquid and air, thereby minimizing surface defects such as orange peel and craters. These additives bind to the binder and functional particles through physical adsorption or chemical reactions, synergistically improving the coating's application performance and appearance. The third stage involves viscosity adjustment and stabilization: an associative polyurethane thickener is added to the system. The hydrophilic groups (such as carboxyl and hydroxyl groups) in its molecular chains combine with water to form a hydration layer, while the hydrophobic groups associate with the hydrophobic portions of the binder's molecular chains (such as the polyurethane backbone) to form a three-dimensional network structure. This network structure increases the system's viscosity through physical entanglement, preventing the functional particles from settling during storage while maintaining the coating's thixotropic properties (high viscosity at rest and low viscosity when stirred), facilitating application and spreadability. Finally, large particles of impurities are removed by filtration to obtain a uniform and stable water-based coating. Its components form a synergistic system through physical dispersion, hydrogen bonding and association, and jointly achieve the dual functions of temperature-sensitive color change and reflective heat insulation.
[0056] According to a preferred embodiment of the present invention, in step S1, the rotation speed of the high-speed disperser is 800-820 rpm; and the pre-dispersion time is 15-20 min.
[0057] According to a preferred embodiment of the present invention, in step S2, the rotation speed of the low-speed stirring is 600-800 rpm, and the time is 5-10 min.
[0058] According to a preferred embodiment of the present invention, in step S3, the pore size of the filter screen is 80-100 mesh.
[0059] The beneficial effects of the present invention are:
[0060] The present invention significantly improves the comprehensive performance of the coating through the coordinated design of dual-functional modified particles, achieving an efficient fusion of temperature-sensitive color change and reflective heat insulation functions. Traditional temperature-sensitive color-changing coatings are prone to uneven color change caused by agglomeration due to the poor compatibility of functional groups with resins. In addition, during long-term use, the groups are easily degraded due to environmental factors (such as ultraviolet rays and humidity), and the color change effect is significantly attenuated. In the present invention, the temperature-sensitive color-changing functional carrier is stably anchored to the surface of nano-scale particles through a special structural design. At the same time, the high specific surface area and surface activity of the inorganic core are utilized to enhance the interfacial bonding force with the water-based resin, effectively avoid agglomeration, and ensure the uniformity of the coating color change. In addition, the chemical stability of the inorganic core and the protective structure of the particle surface work synergistically to significantly improve the weather resistance of the temperature-sensitive group, so that it can still maintain stable color change performance under long-term light, humidity and other environments, solving the pain point of traditional coatings that are easy to fade.
[0061] The optimization of reflective thermal insulation performance is another core advantage of the present invention. Traditional reflective thermal insulation coatings mostly rely on the reflection of near-infrared light by a single filler (such as hollow microspheres), but the filler surface is highly inert, has poor compatibility with the resin, is prone to interfacial peeling, and the reflection efficiency of a single filler is limited. In the present invention, the zwitterionic thermosensitive grafted microspheres can dynamically adjust the surface roughness when the temperature changes through the thermosensitive chain segments grafted on the surface. At low temperatures, the chain segments curl up, the surface of the microspheres is smooth, and heat absorption is reduced; at high temperatures, the chain segments stretch, the surface roughness increases, and the near-infrared reflectivity is further improved. At the same time, the hollow structure inside the microspheres effectively blocks the conduction of heat into the coating. Combined with the high reflective properties of the inorganic core, a dual thermal insulation mechanism of "dynamic reflection + resistance to heat conduction" is formed, which significantly improves the overall thermal insulation efficiency of the coating, which is more than 30% higher than that of traditional single-function coatings.
[0062] The dual-functional design of the present invention also gives the coating excellent comprehensive application performance. The synergistic effect of the two modified particles not only solves the problem of "functional separation" in traditional dual-functional coatings, but also enhances the cohesion of the coating through hydrogen bonding between the zwitterionic groups on the surface of the particles and the water-based resin, giving it better adhesion and impact resistance. In addition, the formulation design of the water-based system avoids the use of organic solvents, significantly reduces the content of volatile organic compounds (VOCs), and meets green environmental protection requirements; the preparation process can be completed through simple mechanical dispersion and blending, without the need for complex equipment and high-temperature reaction conditions, reducing production energy consumption and costs. It is suitable for coating needs in various scenarios such as building exterior walls, industrial equipment, and transportation, and has broad market application prospects. DETAILED DESCRIPTION
[0063] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.
[0064] Example 1
[0065] Preparation of thermochromic-infrared-reflective hybrid nanoparticles: 100 g of indium chloride and 20 g of tin chloride were mixed in 500 mL of ethylene glycol solvent. 10 mL of concentrated hydrochloric acid was added, and the mixture was heated to 181°C and refluxed for 3 hours. Stirring was continued during the reaction to ensure thorough contact between the raw materials. After the reaction, the mixture was transferred to a centrifuge and centrifuged at 10,500 rpm for 15 minutes. The precipitate was collected and washed three times with deionized water (each time with twice the weight of the precipitate) to remove residual hydrochloric acid and unreacted raw materials, resulting in pure ITO nanoparticles. The ITO nanoparticles were dispersed in 200 mL of anhydrous ethanol, and 2 mL of aqueous ammonia was added to adjust the solution pH to 9.0. Subsequently, 50 mL of tetraethyl orthosilicate was slowly added dropwise. The temperature was maintained at 41°C and stirring was continued for 3.5 hours to allow the tetraethyl orthosilicate to hydrolyze and condense to form a SiO2 coating, resulting in SiO2@ITO composite nanoparticles. SiO2@ITO was dispersed in 300 mL of toluene, and 30 mL of aminopropyltriethoxysilane was added. The mixture was heated to 81°C and refluxed for 7 hours to allow aminopropyltriethoxysilane to react with the surface hydroxyl groups of SiO2 to form amino-modified SiO2@ITO. After the reaction, the mixture was centrifuged (10,000 rpm for 10 minutes) and washed. The precipitate was collected and dispersed in 200 mL of anhydrous ethanol. 15 g of spiropyran was added, and the mixture was heated to 61°C for 5 hours to allow the spiropyran and amino groups to undergo a ring-opening reaction, forming a thermochromic group. After the reaction, the mixture was centrifuged (8,000 rpm for 10 minutes) and washed until neutral. The precipitate was transferred to a vacuum drying oven and dried at 41°C for 13 hours. The solvent was removed, and the mixture was ground and passed through a 300-mesh sieve to obtain thermochromic-infrared reflective hybrid nanoparticles of uniform size. Preparation of zwitterionic thermosensitive grafted polymer microspheres: 500 mL of deionized water, 200 g of styrene, and 50 g of sulfobetaine were added to a reactor. Nitrogen was introduced to remove oxygen from the system, followed by the addition of 10 g of potassium persulfate. The reaction was heated to 71°C and maintained for 13 hours. Styrene underwent emulsion polymerization under the action of sulfobetaine, producing polystyrene-sulfobetaine microspheres. The microspheres were then dispersed in 300 mL of N,N-dimethylformamide. 50 g of the thermosensitive monomer N-isopropylacrylamide, 10 mL of ethyl 2-bromoisobutyrate, 2 g of CuBr, and 3 mL of pentamethyldiethylenetriamine were added. The reaction was heated to 61°C and maintained for 25 hours. The thermosensitive monomer was grafted onto the microsphere surface via atom transfer radical polymerization. After the reaction, the mixture was poured into 500 mL of methanol for precipitation. The precipitate was collected by centrifugation (8000 rpm, 10 min) and washed to remove unreacted monomer and solvent, yielding zwitterionic thermosensitive grafted polymer microspheres.Preparation of a thermochromic-reflective and heat-insulating dual-function water-based coating: 300 g of waterborne polyurethane was added to a high-speed disperser, followed by 300 g of deionized water, 120 g of thermochromic-infrared-reflective hybrid nanoparticles, and 250 g of zwitterionic thermosensitive grafted polymer microspheres. Pre-dispersion was performed at 810 rpm for 18 minutes to uniformly disperse the nanoparticles and microspheres in the waterborne polyurethane without significant agglomeration. Subsequently, 30 g of dipropylene glycol butyl ether, 2 g of a silicone defoamer, and 3 g of an acrylic leveling agent were added. The speed was reduced to 650 rpm and stirring was maintained for 7 minutes to ensure uniform mixing of the additives. Finally, 5 g of a di-associative polyurethane thickener was slowly added to adjust the coating viscosity to 60 mPa·s. The coating was filtered through an 80-mesh sieve to remove impurities and packaged.
[0066] Example 2
[0067] The specific implementation method is the same as Example 1, except that the preparation of thermochromic-infrared reflective hybrid nanoparticles is as follows: A1. Indium chloride (120 g) and tin chloride (24 g) are mixed in ethylene glycol (600 mL) and concentrated hydrochloric acid (12 mL) is added. The mixture is refluxed at 180°C for 2 hours. The mixture is then centrifuged (10,000 rpm for 10 minutes) and washed to obtain ITO nanoparticles. The mixture is then dispersed in anhydrous ethanol (250 mL), and the pH is adjusted to 8.9 with aqueous ammonia (3 mL). Ethyl orthosilicate (60 mL) is then added dropwise, and the mixture is stirred at 40°C for 3 hours to obtain SiO2@ITO. A2. The mixture is dispersed in toluene (350 mL), and aminopropyltriethoxysilane (35 mL) is added. The mixture is refluxed at 80°C for 6 hours. The mixture was washed by centrifugation (8000 rpm, 10 min), and spiropyran (18 g) was added. The mixture was reacted at 60°C for 4 h, washed until neutral by centrifugation (8000 rpm, 10 min), dried under vacuum at 40°C for 12 h, and ground through a 320-mesh sieve to obtain thermochromic-infrared reflective hybrid nanoparticles. Preparation of zwitterionic thermosensitive grafted polymer microspheres: B1. Deionized water (600 mL), styrene (250 g), and sulfobetaine (60 g) were added to a reactor, purged with nitrogen, and potassium persulfate (12 g) was added. The reaction was continued at 72°C for 14 h to obtain polystyrene-sulfobetaine microspheres. B2. The mixture was dispersed in N,N-dimethylformamide (400 mL), and a thermosensitive monomer (N-isopropylacrylamide, 60 g), ethyl 2-bromoisobutyrate (12 mL), CuBr (2.5 g), and pentamethyldiethylenetriamine (3.5 mL) were added. The reaction was continued at 62°C for 26 h. Methanol precipitation, centrifugation (8000 rpm, 10 min), and washing yielded zwitterionic thermosensitive grafted polymer microspheres (approximately 300 g). Coating preparation: S1. Pre-disperse deionized water (400 g), nanoparticles (140 g), and microspheres (300 g) in a high-speed disperser (820 rpm) for 20 min. S2. Add dipropylene glycol butyl ether (40 g), defoamer (3 g), and leveling agent (4 g), stirring at 600 rpm for 8 min. S3. Add thickener (6 g) to adjust the viscosity to 70 mPa·s. Filter through an 80-mesh filter and package.
[0068] Example 3
[0069] The specific implementation method is the same as Example 1, except that the preparation of thermochromic-infrared reflective hybrid nanoparticles is as follows: A1: Indium chloride (80g) and tin chloride (16g) are mixed in ethylene glycol (400mL), concentrated hydrochloric acid (8mL) is added, and the mixture is refluxed at 182°C for 4 hours. The mixture is then centrifuged (11000 rpm, 20 minutes) and washed to obtain ITO nanoparticles. The mixture is then dispersed in anhydrous ethanol (150mL), and ammonia (1mL) is added to adjust the pH to 9.1. Ethyl orthosilicate (40mL) is then added dropwise, and the mixture is stirred at 42°C for 4 hours to obtain SiO2@ITO. A2: Indium chloride (80g) and tin chloride (16g) are mixed in ethylene glycol (400mL), concentrated hydrochloric acid (8mL) is added, and the mixture is refluxed at 82°C for 8 hours. The mixture was washed by centrifugation (11,000 rpm, 20 min), and spiropyran (12 g) was added. The mixture was reacted at 62°C for 6 h, washed until neutral by centrifugation (11,000 rpm, 20 min), dried under vacuum at 42°C for 14 h, and ground through a 300-mesh sieve to obtain thermochromic-infrared reflective hybrid nanoparticles. Preparation of zwitterionic thermosensitive grafted polymer microspheres: B1. Deionized water (400 mL), styrene (150 g), and sulfobetaine (40 g) were added to a reactor, purged with nitrogen, and potassium persulfate (8 g) was added. The reaction was continued at 70°C for 12 h to obtain polystyrene-sulfobetaine microspheres. B2. The mixture was dispersed in N,N-dimethylformamide (250 mL), and a thermosensitive monomer (N-isopropylacrylamide, 40 g), ethyl 2-bromoisobutyrate (8 mL), CuBr (1.5 g), and pentamethyldiethylenetriamine (2.5 mL) were added. The reaction was continued at 60°C for 24 h. Methanol precipitation, centrifugation (8000 rpm, 10 min), and washing were performed to obtain zwitterionic thermosensitive grafted polymer microspheres. Coating preparation: S1: Pre-disperse deionized water (250 g), nanoparticles (100 g), and microspheres (200 g) in a high-speed disperser (800 rpm) for 15 min. S2: Add dipropylene glycol butyl ether (20 g), defoamer (1 g), and leveling agent (2 g), stirring at 800 rpm for 5 min. S3: Add thickener (3 g) to adjust the viscosity to 50 mPa·s. Filter through a 100-mesh filter and package.
[0070] Comparative Example 1
[0071] The specific implementation method is the same as Example 1, except that the coating is prepared as follows: S1: Pre-disperse deionized water (300g) and zwitterionic microspheres (250g) in a high-speed disperser (810 rpm) with water-based polyurethane (300g) for 18 minutes. S2: Add dipropylene glycol butyl ether (30g), defoamer (2g), and leveling agent (3g), and stir at 650 rpm for 7 minutes. S3: Add thickener (5g) to adjust the viscosity to 60 mPa·s, filter through an 80-mesh filter, and package (without the thermochromic-infrared-reflecting hybrid nanoparticles).
[0072] Comparative Example 2
[0073] The specific implementation method is the same as Example 1, except that the coating preparation is as follows: S1: Pre-disperse deionized water (300g) and nanoparticles (120g) in a high-speed disperser (810 rpm) with water-based polyurethane (300g) for 18 minutes. S2: Add dipropylene glycol butyl ether (30g), defoamer (2g), and leveling agent (3g), and stir at 650 rpm for 7 minutes. S3: Add thickener (5g) to adjust the viscosity to 60 mPa·s, filter through 80 mesh, and package (without zwitterionic thermosensitive grafted polymer microspheres).
[0074] Comparative Example 3
[0075] The specific implementation method is the same as Example 1, except that the coating preparation is as follows: S1. Pre-disperse water-based polyurethane (300g) in a high-speed disperser (810rpm) with deionized water (300g) for 18 minutes. S2. Add dipropylene glycol butyl ether (30g), defoamer (2g), and leveling agent (3g), and stir at 650rpm for 7 minutes. S3. Add thickener (5g) to adjust the viscosity to 60mPa·s, filter through 80 mesh, and package (without the two modifying ingredients).
[0076] Performance Testing
[0077] The biodegradable composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to the following methods:
[0078] 1. Thermochromic performance test, including the color change temperature range test and the color change reversibility test. The color change temperature range test requires the coating to be evenly applied on an aluminum plate with a thickness of 1mm and a size of 50mm×50mm. After drying for 24 hours, a coating with a thickness of about 200μm is formed. The aluminum plate is placed in a constant temperature box and the temperature is increased from 30℃ to 50℃ in a gradient of 5℃ (30℃, 35℃, 40℃, 45℃, 50℃). The temperature is balanced at each temperature for 10 minutes. The X-Rite The Ci64 colorimeter measures the CIELAB color parameters (L*, a*, b*) of the coating surface, calculates the color contrast before and after color change ΔE*=√[(ΔL*)²+(Δa*)²+(Δb*)²], and determines the color change starting temperature (ΔE*≥5) and the complete color change temperature (ΔE*≥10). The color change reversibility test requires cooling the coating from 45°C to 30°C for 30 minutes, then measuring the color parameters again, and calculating the ΔE before and after cooling to verify whether the color can be reversibly restored.
[0079] 2. Conduct a reflective thermal insulation performance test. Use a Lambda 950 spectrophotometer to measure the reflectivity (R) of the coating in the 380-2500nm band. Calculate the solar reflectance (TSR, where E(λ) is the AM1.5 standard solar spectrum irradiance) according to the formula TSR=∫(380-2500nm)R(λ)·E(λ)dλ / ∫(380-2500nm) E(λ)dλ. An IR-1000 infrared emissivity meter is used to measure the normal emissivity of the coating surface in the 8-13.5μm band, and take the average of five measurements.
[0080] 3. Weathering test: 500 hours of aging were performed using a Q-Lab QUV / se accelerated aging tester in accordance with GB / T 1865-2009 (UV lamp wavelength 340nm, irradiance 0.89W / m², blackboard temperature 65°C, condensation cycle 4 hours (40°C deionized water spray)). The gloss retention after aging ((reflectance after aging / initial reflectance) × 100%) and color change ΔE were tested.
[0081] 4. Conventional performance tests, including adhesion (testing the adhesion between the coating and the aluminum plate using the cross-hatch method (2mm spacing) in accordance with GB / T 3186-2020. Observe whether the edges of the grid are peeling, and grade the test on a scale of 1-5 (1 being the worst and 5 being the best)), water resistance (immerse the coated sample in deionized water. After 72 hours, observe whether the surface has blistering or peeling, and record whether it passes or fails). Drying time (testing the surface dry time using the finger touch method (no fingerprints when lightly pressed with a finger) and the scraper method (no sticking when lightly scratched with a scraper) in accordance with GB / T 1728-1989).
[0082] 5. Performance test results:
[0083] Table 1: Performance test results of various embodiments and comparative examples
[0084] Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Color change temperature range (℃) 32-45 30-44 31-46 No discoloration 32-45 No discoloration Complete color change ΔE* (45℃) 12.3 11.9 12.1 — 8.7 — ΔE* after cooling (30℃) 11.8 11.5 11.7 — 7.2 — Solar reflectance (TSR) 0.85 0.86 0.84 0.72 0.68 0.55 Hemispherical emissivity (ε) 0.88 0.87 0.89 0.82 0.85 0.79 500h gloss retention rate (%) 88 86 85 82 75 68 500h color ΔE* 2.1 2.3 2.2 0.5 4.5 6.8 Adhesion (grade) 5 5 5 5 5 4 Water resistance (72h) qualified qualified qualified qualified qualified Slight bubbling on the edges Surface drying time (min) 45 50 48 45 45 45 Drying time (h) 2 2 2 2 2 2
[0085] As shown in Table 1, the performance results of Examples 1-3 demonstrate that, through the collaborative design of dual-modified compounds, the present invention effectively addresses core issues such as the functional separation, poor compatibility, and insufficient weather resistance of traditional thermochromic coatings and reflective thermal insulation coatings. Specifically, the color change temperature range of Examples 1-3 is concentrated between 30-46°C (ΔE* ≥ 11.8), far exceeding the color change sensitivity of traditional thermochromic coatings (typically ΔE* ≤ 10). Furthermore, the color can be reversibly restored upon cooling (ΔE* ≤ 2.3). This demonstrates that the thermochromic group is stably anchored by the hybrid particles, avoiding the problem of uneven color change caused by agglomeration. Furthermore, the dynamic ring-opening / closing reaction of the spiropyran group maintains good reversibility. In terms of reflective and thermal insulation performance, the solar reflectance (TSR) of Examples 1-3 reached 0.84-0.86, and the hemispherical emissivity (ε) was 0.87-0.89, which were significantly higher than those of Comparative Example 1 (without thermosensitive particles, TSR=0.72) and Comparative Example 2 (without amphoteric microspheres, TSR=0.68). This shows that the zwitterionic thermosensitive grafted microspheres achieve the dual effects of "dynamic reflection + passive thermal insulation" through the dynamic regulation of the surface thermosensitive segments (the low-temperature segments curl up to reduce heat absorption, and the high-temperature segments stretch to enhance reflection) and the heat resistance conduction of the hollow structure, thus solving the problem of low reflection efficiency of traditional single fillers. Furthermore, the 500h gloss retention of Examples 1-3 reached 85-88%, significantly higher than that of Comparative Example 3 (no modified component, gloss retention 68%). Furthermore, the adhesion remained stable at Level 5 (optimal level), and the water resistance was acceptable. This demonstrates that the dual-modified particles, through hydrogen bonding between the surface zwitterionic groups and the waterborne resin, combined with the high chemical stability of the inorganic core, significantly enhance the interfacial bonding and weather resistance of the coating and resin, resolving the long-term performance degradation issue of traditional dual-functional coatings due to functional group incompatibility. In summary, through the dual-modification design of "thermochromic-infrared reflective hybrid nanoparticles + zwitterionic thermosensitive grafted polymer microspheres," Examples 1-3 achieve efficient synergy between thermochromic and reflective heat-insulating functions, while overcoming the pain points of traditional coatings, such as functional fragmentation, poor compatibility, and insufficient weather resistance.
[0086] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. A temperature-sensitive color-changing and reflective heat-insulating dual-function water-based coating, characterized in that: The invention comprises the following raw materials in parts by weight: Waterborne polyurethane: 250-450 parts by weight; Thermochromic-infrared reflective hybrid nanoparticles: 50-100 parts by weight; Zwitterionic thermosensitive grafted polymer microspheres: 200-350 parts by weight; Dipropylene glycol butyl ether: 20-50 parts by weight; Silicone defoamer: 1-3 parts by weight; Acrylate leveling agent: 2-5 parts by weight; Biassociative polyurethane thickener: 3-8 parts by weight; Deionized water: 250-400 parts by weight; Among them, the preparation method of the thermosensitive color-changing-infrared reflective hybrid nanoparticles includes: A1, mixing indium chloride and tin chloride in ethylene glycol solvent, adding concentrated hydrochloric acid, reflux reaction at 180-182°C, and centrifugation and washing to obtain ITO nanoparticles; dispersing the ITO nanoparticles in anhydrous ethanol, adding ammonia water to adjust the pH to 8.9-9.1, slowly adding tetraethyl orthosilicate, and stirring at 40-42°C to obtain SiO2@ITO; A2, dispersing SiO2@ITO in toluene, adding aminopropyltriethoxysilane, reflux reaction at 80-82°C, and centrifugation and washing to obtain amino-modified SiO2@ITO; dispersing the amino-modified SiO2@ITO in anhydrous ethanol, adding spiropyran, reacting at 60-62°C, centrifugation and washing until neutral, vacuum drying at 40-42°C, and grinding and sieving.
2. The temperature-sensitive color-changing and reflective heat-insulating dual-function water-based paint according to claim 1, characterized in that: In step A1, the reaction time is 2-4 hours at 180-182°C under reflux; the centrifugation speed is 10000-11000 rpm and the reaction time is 10-20 minutes; The stirring time at 40-42℃ is 3-4h.
3. The temperature-sensitive color-changing and reflective heat-insulating dual-function water-based paint according to claim 1, characterized in that: In step A2, the reflux reaction time at 80-82° C. is 6-8 h; the reaction time at 60-62° C. is 4-6 h; the vacuum drying time at 40-42° C. is 12-14 h; and the product is ground through a 300-320 mesh sieve.
4. The temperature-sensitive color-changing and reflective heat-insulating dual-function water-based paint according to claim 1, characterized in that: The preparation method of the zwitterionic thermosensitive grafted polymer microspheres comprises the following steps: B1, adding deionized water, styrene, and sulfobetaine into a reactor, passing nitrogen to remove oxygen, adding potassium persulfate, and reacting at 70-72° C. to obtain polystyrene-sulfobetaine microspheres; B2, dispersing the polystyrene-sulfobetaine microspheres in N,N-dimethylformamide, adding a thermosensitive monomer, ethyl 2-bromoisobutyrate, CuBr, and pentamethyldiethylenetriamine, and reacting at 60-62° C.; and after the reaction, precipitating with methanol and washing by centrifugation.
5. The temperature-sensitive color-changing and reflective heat-insulating dual-function water-based paint according to claim 4, characterized in that: In step B1, the reaction time at 70-72° C. is 12-14 h.
6. The temperature-sensitive color-changing and reflective heat-insulating dual-function water-based paint according to claim 4, characterized in that: In step B2, the reaction time at 60-62° C. is 24-26 h.
7. A method for preparing the temperature-sensitive color-changing and reflective heat-insulating dual-function water-based coating according to any one of claims 1 to 6, characterized in that the steps include: S1. Add waterborne polyurethane to a high-speed disperser, followed by deionized water, thermochromic-infrared reflective hybrid nanoparticles, and zwitterionic thermosensitive grafted polymer microspheres, and pre-disperse until no obvious agglomeration occurs. S2. Add dipropylene glycol butyl ether, silicone defoamer, and acrylic leveling agent and stir at low speed; S3. Slowly add associative polyurethane thickener to adjust the viscosity to 50-80 mPa·s, filter and package.
8. The preparation method according to claim 7, characterized in that In step S1, the rotation speed of the high-speed disperser is 800-820 rpm; the pre-dispersion time is 15-20 min.
9. The preparation method according to claim 7, characterized in that In step S2, the rotation speed of low-speed stirring is 600-800 rpm, and the time is 5-10 minutes.
10. The preparation method according to claim 7, characterized in that In step S3, the pore size of the filter screen is 80-100 mesh.